The evolution of the histopathologic classification of thymic epithelial tumors - Marino, Mirella; Roden, Anja C. (Mediastinum; Vol 2 (March 2018): Mediastinum, 2018)
Few topics in pathology have been as controversial as the classification of thymic epithelial tumors (TET). The lack of knowledge regarding the structure and function of the thymus has certainly contributed to this difficulty. Only in the second part of the 20th century did a new awareness concerning the importance of the thymus emerge. Moreover, the heterogeneity of the histopathologic features and the variability of the lymphocytic content in TET contributed to an increase in the number of histologic classifications. This review covers the main classifications and points out the people who developed several classification schema and their underlying “driving” concepts. Historically, the first step regarded the need to separate TET from other tumors occurring in the mediastinum. Subsequently the discussion focused on establishing TET types or subtypes with different prognostic value. The development of histopathologic classifications of TET took also advantage of progressing advances in the knowledge of the thymus together with the adoption of new diagnostic tools which increased diagnostic accuracy and reproducibility. The ultimate goal of the diagnostic pathological process, from the very beginning, was to provide the most useful information to the clinicians (thoracic surgeons, oncologists) involved in patient management.